Immunonutrition and Hepatoprotectant Aspects of Moringa Oleifera Leaf Nanoemulsion Syrup as an Antituberculosis Adjuvant for Children with Tuberculosis - Nyoman Budhi Wirananda Setiawan; Agus Indra Yudhistira Diva Putra; Made Indira Dianti Sanjiwani; Agung Wiwiek Indrayani; Ida Ayu Ika Wahyuniari (Universitas Gadjah Mada, 2022)
Tuberculosis in children is a global health problem that decreases the quality of life of children. Based on data from the Indonesian Ministry of Health in 2016, nearly 69.000 children had tuberculosis and the case keeps increasing every year. Moringa oleifera leaf nanoemulsion syrup has immunonutrition and hepatoprotectant effects in children with tuberculosis. Moringa oleifera leaf nanoemulsion syrup contains proteins, micronutrients, and minerals which have a biological role as an immunity agent and prevent toxic effects of tuberculosis drugs. Until now, the use of Moringa oleifera leaf nanoemulsion syrup has been carried out for the immunomodulatory and hepatoprotective aspects. Immunomodulatory and hepatoprotective aspects will be discussed further in this literature review. The sources of articles in this literature review are pubmed.com, ncbi.com, plosone.com, sciencedirect.com, and googleschoolar.com from 2010-2020, except when there is no new research against the article. The authors searched for the keywords: